Oral cleanliness of 12-13-year-old and 15-year-old school children of Sunsari District, Nepal - Yee R; David J; Khadka R (Wolters Kluwer Medknow Publications, 2006)
The aim of the study was to evaluate the oral cleanliness of school children in the District of Sunsari, Nepal. A multi-stage random sampling oral epidemiological survey was conducted in private and government, urban, rural town and rural village schools in 15 illakas of Sunsari District, Eastern Nepal. A total of 600, 12-13-year-old and 600 15-year-old school children were examined by trained examiners using the simplified oral hygiene index (OHI-S). The average age-group, debris and calculus index scores were combined to obtain the simplified oral hygiene index (OHI-S). The mean OHI-S scores were compared and evaluated using the parametric t-test for two independent samples. The mean OHI-S for urban 12-13-year-old school children was 0.98 compared to 1.34 for school children of rural towns and 1.44 for school children of rural villages and these differences in mean OHI-S were statistically significant ( P < 0.005). In the 15-year-old age group, urban school children had a mean OHI-S score of 1.00 compared to 1.37 for rural towns and 1.43 for rural villages. The variance in the mean OHI-S scores were statistically significant ( P < 0.005). The overall level of cleanliness in the school children surveyed was good. Children of urban schools had the lowest scores followed by school children from rural towns and then rural villages. When the mean OHI-S scores were compared with the DMFT scores, there was an inverse relationship between oral cleanliness and dental caries. Frequency of sugar consumption and the availability and affordability of fluoridated toothpaste may be important factors in the development of dental caries than oral cleanliness.